Ann Med Lab Sci 2021
DOI: 10.51374/annalsmls.2021.1.1.0018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IgM and IgG Dengue antibodies in febrile patients suspected of malaria attending health center in Jos, Nigeria

Abstract: Background: Despite the public health importance of dengue infections, it is less investigated by clinicians and rarely considered in the differential diagnosis of febrile illnesses in Nigeria. The objective was to detect the presence of Dengue IgG/IgM antibodies and Plasmodium species in the blood of febrile patients. Methods: This is a cross sectional study conducted among ninety-four (94) consenting febrile patients suspected of malaria in Jos. Duo detection of dengue antibodies (IgG/IgM) were determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Cross-sectional studies in Kenya [22, 39] and Cameroon [30, 45] reported significantly low odds of acute dengue in the presence of malaria than in its absence (OR = 0.57, 95% CI, 0.40 – 0.82). Similar studies Nigeria [18, 20, 25, 32, 33, 35], Tanzania [17], Sierra Leone [23], DRC [34], Cameroon [31], Sudan [40, 42], and Senegal [21] ; however, showed no notable odds of acute dengue infection in the presence of malaria when compared to the absence of malaria (OR = 1.07, 95% CI, 0.58 –1.94). On the contrary, cross-sectional studies in Ethiopia [44], Nigeria [16, 29], Tanzania [36], and Cameroon [43] indicated higher odds of acute dengue infection in the presence of malaria than in its absence (OR = 6.98, 95% CI, 2.89 – 16.85).…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…Cross-sectional studies in Kenya [22, 39] and Cameroon [30, 45] reported significantly low odds of acute dengue in the presence of malaria than in its absence (OR = 0.57, 95% CI, 0.40 – 0.82). Similar studies Nigeria [18, 20, 25, 32, 33, 35], Tanzania [17], Sierra Leone [23], DRC [34], Cameroon [31], Sudan [40, 42], and Senegal [21] ; however, showed no notable odds of acute dengue infection in the presence of malaria when compared to the absence of malaria (OR = 1.07, 95% CI, 0.58 –1.94). On the contrary, cross-sectional studies in Ethiopia [44], Nigeria [16, 29], Tanzania [36], and Cameroon [43] indicated higher odds of acute dengue infection in the presence of malaria than in its absence (OR = 6.98, 95% CI, 2.89 – 16.85).…”
Section: Resultssupporting
confidence: 77%
“…Cross-sectional studies in Kenya [22,39] and Cameroon [30,45] reported significantly low odds of acute dengue in the presence of malaria than in its absence (OR = 0.57, 95% CI, 0.40 -0.82). Similar studies Nigeria [18,20,25,32,33,35],…”
Section: The Interaction Of Plasmodium and Dengue Virusessupporting
confidence: 72%
See 3 more Smart Citations